TEACHING READING THROUGH THREE STAY ONE STRAY TOWARDS AT MA DARUSOLLIHIN NW KALIJAGA - Muhlisin, Muhammad; Aprianoto, Aprianoto (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
This investigation deal with quasi experimental in the form non-randomize control group design or non-equivalent by purposing at finding out teaching reading through three stay one stray. The investigation used total sampling technique in determining the sample of the research. The data was taken by using test in the form of multiples choice and it analyzed by using descriptive statistic and inferential analysis. Based on the data analysis was gotten that the result of analysis shown that t-test was higher than t-table. It can be inferred that alternative hypothesis accepted and null hypothesis rejected. Therefore, it concluded that there was significant effect teaching reading through three stay one stray